The Cutting in the Fold - Yansyah, Andri; Maryani, Lesi (The International Journal of Pegon : Islam Nusantara civilization, 2024)
This article discusses the Kiai Protest Movement in East Java in the late nineteenth and early twentieth centuries, with a focus on the ability of the Kiai as a social elite to utilise their position in resistance to Dutch colonialism. Kiai, as religious and intellectual figures in pesantren, had significant social influence in East Javanese society. This article explains how the Kiai used their influence and authority to lead protest and anti-colonialism movements. By analysing how Kiai used their social standing to resist the Dutch, this article provides a deeper understanding of the key role of Kiai in protest and anti-colonial movements in East Java. It also reveals the complexity of the social and political dynamics of the period, in which religious elites such as Kiai played a pivotal role in the struggle against foreign colonialism. Artikel ini membahas tentang Gerakan Protes Kiai di Jawa Timur pada akhir abad XIX dan awal abad XX, dengan fokus pada kemampuan Kiai sebagai elite sosial dalam memanfaatkan posisinya dalam perlawanan terhadap kolonialisme Belanda. Kiai sebagai tokoh agama dan intelektual di pesantren mempunyai pengaruh sosial yang signifikan dalam masyarakat Jawa Timur. Artikel ini menjelaskan bagaimana Kiai menggunakan pengaruh dan wewenangnya untuk memimpin gerakan protes dan anti-kolonialisme. Dengan menganalisis bagaimana Kiai menggunakan status sosialnya untuk melawan Belanda. artikel ini memberikan pemahaman yang lebih mendalam tentang peran kunci Kiai dalam gerakan protes dan anti-kolonial di Jawa Timur. Hal ini juga mengungkap kompleksitas dinamika sosial dan politik pada masa tersebut, di mana elit agama seperti Kiai memainkan peran penting dalam perjuangan melawan kolonialisme asing.